Genetic Contribution of Synapse-Associated Protein 97 to Orbitofrontal–Striatal–Thalamic Circuitry Connectivity Changes in First-Episode Schizophrenia - Xu, Xusan; Luo, Shucun; Wen, Xia; Wang, Xiaoxia; Yin, Jingwen; Luo, Xudong; He, Bin; Liang, Chunmei; Xiong, Susu; Zhu, Dongjian; Fu, Jiawu; Lv, Dong; et al. (Frontiers in Psychiatry, 2021)
Functional and structural disturbances in the orbitofrontal-striatal-thalamic circuitry are thought to be associated with mental symptoms and neurocognitive impairments in schizophrenia. This study tested whether synapse-associated protein 97 (SAP97), a reasonable candidate gene for schizophrenia, is related to orbitofrontal-striatal-thalamic connection changes in first-episode schizophrenia (FES) patients and the clinical performance of schizophrenic patients by affecting this integrity. Fifty-two FES patients and 52 matched healthy controls (HCs) were recruited. All subjects underwent genotyping via the improved multiplex ligation detection reaction (imLDR) technique and scanning with magnetic resonance imaging (MRI) to provide orbitofrontal-striatal-thalamic functional and structural imaging data. A two-way ANCOVA model was employed to examine abnormal brain connectivities, and Spearman correlations were applied to estimate the relationships between brain connectivity and clinical manifestations. In the FES group, those with the SAP97 rs3915512 TT genotype showed lower structural and functional connectivity than A allele carriers between the orbitofrontal gyrus and striatum/thalamus. In the FES group, negative correlations were found between resting-state functional connectivity (RSFC) in the orbitofrontal gyrus and thalamus and positive symptoms and between structural connections in the orbitofrontal gyrus and striatum and cognitive functions, and positive correlations were suggested between RSFC in the orbitofrontal gyrus and thalamus and negative symptoms. Our findings suggested that the SAP97 rs3915512 polymorphism may be involved in mental symptoms and cognitive dysfunction in FES patients by influencing structural and functional connectivity of the orbitofrontal-striatal and orbitofrontal-thalamic regions.